On Problem of Training of Professional Commentators of Computer Sports (e-Sports) - P. A. Sukhodimtsev (Научный диалог, 2018)
The theoretical basis of the profession of commentator of computer sports in the post-industrial society is considered. It is emphasized that the system of professional education should focus on training e-sports specialists, which are in dire need of the computer sports industry. It is proved that at the present time the training of professional athletes of e-sports in general and commentators in particular is fragmentary. The review of scientific literature is carried out. It is shown that in the scientific environment this problem is practically not considered. Definitions of the terms “e-sports” / “computer sports” etc. are given. The author describes the activities of e-sports commentator in terms of competitiveness of a specialist in the labor market. Understanding of the activities of e-sports commentator specializing in the subject “Counter-Strike: Global Offensive” is detailed. The novelty of the research is that the author offers a three-level competence model of training a professional commentator of e-sports at a university. The content of the educational module is described, created on the basis of the model, tested in part in the professional activities of the author of this article as a sport commentator of “Counter-Strike: Global Offensive” in open company “Ruhab.”